2020
DOI: 10.1016/j.ebiom.2020.103078
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus genomic load and disease severity among children hospitalised with hand, foot and mouth disease

Abstract: Background: Examining associations between viral genomic loads of enteroviruses and clinical severity is important for promoting and improving development of antiviral drugs related to hand, foot and mouth disease (HFMD). Methods: Throat swabs were collected from HFMD cases at acute phase of illness using a standardized technique in a prospective study. The viral genomic load was categorized into low, medium, and high groups using parameters of real-time reverse transcription-polymerase chain reaction. The cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Based on our study, 56.7% of the specimens were positive for anti-EV-A71 antibodies, which means that EV-A71 has had a circulation in our society. Our finding is consistent with few reports of EV-A71 in neurological diseases and no reports of HFMD cases with EV-A71 ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…Based on our study, 56.7% of the specimens were positive for anti-EV-A71 antibodies, which means that EV-A71 has had a circulation in our society. Our finding is consistent with few reports of EV-A71 in neurological diseases and no reports of HFMD cases with EV-A71 ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, due to the characteristic of low viral loads in CSF, the detection rate of pathogens is underestimated and the definite pathogen diagnoses are insufficient [ 2 ]. Moreover, it’s reported that the viral loads can assess disease severity and predict clinical outcomes [ 9 ]. Thus, a highly sensitive approach with strong quantitative ability is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, parechovirus makes almost equal contributions to CNS infection compared with EV [ 8 ]. The CNS of children is susceptible to EV and HPeV, and HSV encephalitis is common in both children and the elderly [ 9 11 ]. As these infections may lead to serious sequelae, prompt recognition and treatment are crucial for patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enteroviruses are known to have vast variations in their genomes ( Simmonds et al. 2006 ) and are prone to recombination events, which have been suggested to be a driving force for evolution ( Song et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%